GRAFTING OF BIOMODELS PRODUCED BY ADDITIVE MANUFACTURING USING ACRYLONITRILE BUTADIENE STYRENE (ABS) IN RABBIT TIBIAS - do Prado, Tales Dias; Silva, Taiane Santos; Prates, Yasmin Souza; Honório, Andressa dos Santos; da Silva, Maise Medeiros Gomes; Caldas, Suzana Maira da Silva; dos Santos, Marcelo Augusto Rozan; Treichel, Tiago Luís Eilers (Seven Editora, 2026)
Additive manufacturing has emerged as a promising technology in the healthcare field, particularly in the development of biomodels and customized implants. This study aimed to evaluate the use of acrylonitrile butadiene styrene (ABS) biomodels produced by 3D printing as grafts in rabbit tibias. Six New Zealand rabbits were used, receiving screw- shaped implants measuring 7 mm in length. The implants were sterilized either by autoclaving or immersion in glutaraldehyde. Animals were clinically evaluated until the third postoperative day and radiographically assessed at 0, 30, and 60 days. After this period, euthanasia was performed followed by macroscopic evaluation of the implants. ABS demonstrated low tissue reactivity, absence of rejection, and signs of osteointegration. Although autoclave sterilization resulted in slight deformation, it did not impair implantation. These findings suggest that ABS has potential for use in the development of customized orthopedic implants, although further long-term studies are required.